Application of Interval Training Method to Improve Anaerobic Alactacid Capacity - Salsa Loka Nuari Malik; Dikdik Zafar Sidik; Nida'ul Hidayah; Fitri Rosdiana (Journal of Physical Education Health and Sport, 2025)
This study aims to examine the effect of the application of the interval training method on increasing anaerobic alactitic capacity in female futsal athletes. Anaerobic alactitic capacity is one of the components of physical condition that is very important in supporting futsal performance, especially in short-duration explosive activities such as sprints, accelerations, and rapid changes of direction that occur repeatedly during the match. The research method used is an experimental method with a one-group pre-test post-test design. The research subjects were 21 female futsal athletes selected using a purposive sampling technique from a total population of 24 athletes, with the criteria of actively participating in training and being in healthy physical condition. The instrument used to measure anaerobic alactitic capacity was the Shuttle Run Test. The interval training program was implemented in a structured manner for 16 meetings with high intensity and controlled recovery time. Data analysis was carried out through descriptive tests to see the data overview, normality tests as a prerequisite for analysis, and paired sample t-tests to test differences in pre-test and post-test values. The results showed a significant improvement in anaerobic alactitic capacity, indicated by a decrease in the mean Shuttle Run Test time from 6.75 seconds in the pre-test to 6.46 seconds in the post-test. The paired sample t-test analysis revealed a significant difference between pre-test and post-test scores (p < 0.05), confirming that the application of the interval training method had a significant effect on increasing anaerobic alactacid capacity in female futsal athletes.